1981
DOI: 10.1177/009385488100800202
|View full text |Cite
|
Sign up to set email alerts
|

Pedophilia and Aggression

Abstract: While some authors consider pedophiles to be physically harmless individuals who do not attempt intercourse with their often seductive victims, others have identified a minority of child molesters who are aggressively predatory. Data from penitentiary files revealed that 29 of 41 incarcerated pedophiles used threats of violence or actual physical force to secure their sexual goals, and these sexual goals frequently involved penile penetration. Those inmates who did use force were also generally criminal in ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…We would expect this not just because of their anger toward women but also because loneliness is strongly associated with a tendency to be aggressive (Check et al, 1985;Zilboorg, 1938). Consistent with this suggestion, sexual offenders have been found to be far more aggressive in their assaults than is necessary to achieve their goal of sexual contact (Christie et al, 1979;Groth, 1979;Marshall and Christie, 1981). Of course, if sexual offending originates, at least in part, because of low levels of self-worth, then a continued lack of sell-esteem should perpetuate the unsavoury behavior once the felon learns that he can circumvent his lack of confidence by offending.…”
Section: Self-esteem and Its Relationshipmentioning
confidence: 95%
“…We would expect this not just because of their anger toward women but also because loneliness is strongly associated with a tendency to be aggressive (Check et al, 1985;Zilboorg, 1938). Consistent with this suggestion, sexual offenders have been found to be far more aggressive in their assaults than is necessary to achieve their goal of sexual contact (Christie et al, 1979;Groth, 1979;Marshall and Christie, 1981). Of course, if sexual offending originates, at least in part, because of low levels of self-worth, then a continued lack of sell-esteem should perpetuate the unsavoury behavior once the felon learns that he can circumvent his lack of confidence by offending.…”
Section: Self-esteem and Its Relationshipmentioning
confidence: 95%
“…Marshall and Christie (1981) reported that some 70% of a group of 41 incarcerated child molesters had either threatened or used physical violence in the commission of their offenses. For about 28% of the sample, no evidence could be found for the use of either verbal or physical aggression.…”
mentioning
confidence: 99%
“…Christie et al (1979) and Marshall and Christie (1981) reported that 36% of child molesters had intercourse with their child victims. Although intercourse is more likely to occur when the children are 10 years or older, many younger victims are also forced to engage in vaginal or anal intercourse.…”
mentioning
confidence: 99%